Modeling Population Growth and Response to Harvest for River Otters in Illinois. (April 2016) - Nielsen, Clayton K.
Abstract: Population modeling is an invaluable tool for predicting wildlife population dynamics and the effects of management. I created a state‐space population model for unharvested river otters in the Illinois, Kaskaskia, and Wabash river basins in Illinois, and modeled future harvest at 5%, 10%, and 20% levels. River otter populations increased in the absence of harvest during 2000 – 2009 to 8, 408 ± 1, 934 individuals (λ = 1.11 ± 0.09). Harvest at 0%, 5%, 10%, and 20% levels resulted in continued population growth over time, with annual harvest numbers ranging from 446 – 1, 786 in 2010 to 884 – 2, 614 in 2014, depending on harvest scenario. I concluded that river otter populations in Illinois were thriving and capable of withstanding a regulated harvest.